Ghana : Improving the Targeting of Social Programs - World Bank (World Bank, 2012)
This study, a draft of which was shared with the Government of Ghana in November 2009, provides a basic diagnostic of the benefit incidence and targeting performance of a large number of social programs in Ghana. Both broad-based programs (such as spending for education and health, and subsidies for food, oil-related products, and electricity) as well as targeted programs (such as Livelihood Empowerment against Poverty, or LEAP, the indigent exemption under the National Health Insurance Scheme (NHIS), school lunches and uniforms, or fertilizer subsidies) are considered. In addition, the study provides tools and recommendations for better targeting of those programs in the future. The tools include new maps and data sets for geographic targeting according to poverty and food security, as well as ways to implement proxy means-testing. This executive summary provides a brief synthesis of the key findings and messages from the study.